Passive and Thermo-Optic Characterization of Long-Range Surface Plasmon-Polariton Structures in CYTOP - Fan, Hui (Université d'Ottawa / University of Ottawa, 2011)
Long-range surface plasmon-polariton waveguides fabricated of gold, cladded with CYTOP, designed to be 5μm wide and 35nm thick, were modelled and fabricated by other researchers and tested by the author. In passive measurements, cutback curves were drawn and S-bends, Y-junctions, Mach-Zehnder interferometers, and couplers were tested. Results show that the fabricated waveguide thicknesses are inconsistent and thinner than designed, and improvement of their fabrication quality is necessary. In thermo-optic measurements, electric currents were injected heating the waveguides and changing the refractive index of the claddings. Electromigration were characterized and the conclusion was that the waveguides can work under the current density 70GA/m2. Mode extinction experiments were made and as one waveguide was repeatedly tested its mode extinction threshold gradually decreased due to heat accumulation and CYTOP glass-transition. 2.5mA was safe to prevent mode extinction in the first 12 experiments. The optical response time was also measured and discussed.